Bioconstruction and Bioerosion in the Northern Adriatic Coralligenous Reefs Quantified by X-Ray Computed Tomography - Turicchia, Eva; Abbiati, Marco; Bettuzzi, Matteo; Calcinai, Barbara; Morigi, Maria Pia; Summers, Adam P.; Ponti, Massimo (Frontiers in Marine Science, 2022)
The northern Adriatic continental shelf hosts several coralligenous reefs rising from the sedimentary bottom and characterized by three main benthic assemblages, respectively, dominated by algal turfs, encrusting calcareous rhodophyte (ECRs) or erect sponges. Bioconstruction and bioerosion processes have been investigated using recruitment travertine limestone tiles deployed in a random site for each main benthic assemblages off Chioggia, 6.1–14.4 km offshore and 20.2–25.4 m depth. Tiles were retrieved after 3 and 12 years and analyzed by X-ray computed tomography (CT), allowing for non-destructively identifying and quantifying deposited and eroded limestone. The main builders were ECRs, serpulids, bryozoans, barnacles, and the bivalves Anomia ephippium, while the most effective borers were sponges from the genus Cliona and the bivalve Rocellaria dubia. The deposition of limestone after 12 years was greater at the site MR08 dominated by ECRs (12.52 ± 2.22 kg m–2), intermediate at the site P213 dominated by erect sponges (4.20 ± 1.24 kg m–2), and lower in the site P204 dominated by algal turfs (2.20 ± 0.72 kg m–2). At MR08, the deposition rate did not vary much over time (from 1.295 ± 0.270 to 1.080 ± 0.198 kg m–2 a–1), while in the other two sites, it significantly slowed down after the first survey period: from 0.952 ± 0.199 to 0.350 ± 0.103 kg m–2 a–1 at P213, and from 1.470 ± 0.462 to 0.203 ± 0.058 kg m–2 a–1 at P204. The amount of eroded limestone increased with the exposure time, with no significant differences among sites, from 1.13 ± 0.29 to 10.39 ± 1.14 kg m–2 on average at 3 and 12 years, respectively. The bioerosion rate also increased with the exposure time and was slightly higher at MR08 (from 0.682 ± 0.208 to 1.105 ± 0.088 kg m–2 a–1), mostly eroded by Cliona rhodensis in addition to C. viridis, compared to P204 (from 0.267 ± 0.078 to 0.676 ± 0.172 kg m–2 a–1) and P213 (from 0.179 ± 0.065 to 0.816 ± 0.171 kg m–2 a–1). Overall, bioconstruction has overcome the bioerosion processes in 3 years. In 12 years, the estimated net balance was essentially nil at all sites. Combining field experiment and CT analysis, this study provides the first quantification of the bioerosion and bioconstruction processes in the northern Adriatic coralligenous reefs, a fundamental step toward their conservation.